The Legal Consequences of Default in Consumer Financing with Fiduciary Guarantees by Debtors - Khalisah Hayatuddin; Abdul Latif Mahfuz; Sanjaya Putra; Muhamad Sadi Is (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2024)
Providing the financing with a fiduciary charge will make it easy for the consumer. Not only they can get a loan, but they also retain possession of the collateral. However, if there is a default in consumer financing with a fiduciary guarantee by the debtor, it often creates legal consequences in practice. The focus of this paper is on legal consequences for parties who default on consumer financing with fiduciary guarantees. This type of normative research looks at legal provisions regarding creditor and debtor agreements on fiduciary guarantees. Thus, the conclusion was due to the law that there was a default in consumer financing with fiduciary guarantees that was able to collect bills. If repayment was not made, the creditor would sell collateral goods.